Impact of immunodeficiencies on immunity induced by SARS-CoV-2 infection, mRNA BNT162b2 vaccination, and their combination in children and young adults - Fialova, Lubica; Macek-Nabova, Birivan; Zilkova, Monika; Turic-Csokova, Natalia; Palova, Denisa; Katina, Stanislav; Paulikova-Rolkova, Gabriela; Ciznar, Peter; Horakova, Julia; Wojciakova, Lubica; Markova, Karina; Kontsekova, Eva; et al. (Frontiers in Immunology, 2025)
Current understanding of how immunodeficiencies impact protective responses against viral infections and vaccination is primarily derived from adult cohorts that may not accurately reflect the pediatric, adolescent, and young adult population. This cross-sectional study aimed to evaluate immune responses in this underrepresented population affected by various immunodeficiencies after SARS-CoV-2 infection, two doses of the mRNA BNT162b2 vaccine, or after a combination of both. We analyzed blood samples from 102 immunocompromised patients (IC) (5–25 years) categorized into groups of primary immunodeficiencies (PID, n=17), bronchial asthma and allergic rhinitis (BA-AR, n=39), rheumatoid diseases (RD, n=21), and individuals who had undergone hematopoietic stem cell transplantation (HSCT, n=28), as well as 30 healthy individuals (9–26 years). We measured titres of Spike-specific IgM, IgA, and IgG antibody classes (including IgG subclasses) in plasma using ELISA and evaluated their inhibitory potential in a Spike-ACE2 cell-based internalization assay. Spike-specific CD4 T-cells were examined using a flow cytometry-based proliferation assay (FASCIA). In the IC group, all participants except eight generated detectable levels of IgG antibodies. The IgG titres induced by vaccination (Geometric mean titre (GMTvac) = 205023, 95% CI: 116074-362136) and a combination of vaccination and infection (GMThyb = 172819, 95% CI: 33133-901403) were higher than after infection (GMTinf = 3323, 95% CI: 578-19109, Pvac/inf = .006 and Phyb/inf = .001). On the other hand, the hybrid immunity induced the highest IgA titres (GMThyb = 2672, 95% CI: 566-12623) compared to vaccination (GMPvac = 275, 95% CI: 97-777, Phyb/vac = .016) and infection (GMTinf = 60, 95% CI: 13-280, Phyb/inf = .002). The IgG titres in vaccinated and hybrid immunity groups strongly correlated (rSpearman = 0.86, P <.0001) with the levels of antibodies inhibiting the internalization of Spike protein (S protein) in a cell-based assay. Most IC patients (except five) also developed above-threshold Spike-specific CD4 T-cell responses, which were not statistically different from the responses in the healthy control group. Our data show that infection and vaccination can induce protective humoral or cellular responses against SARS-CoV-2 in IC patients. The activated cellular response in patients with agammaglobulinemia may assist them in overcoming viral infections.